Overhead costs and profit calculation by Polish contractors - Plebankiewicz, Edyta; Leśniak, Agnieszka (Technological and Economic Development of Economy, 2013)
The main criterion taken into consideration when choosing a contractor is the bid price that the contractor suggests. The basis for determining such a price are the direct costs connected with works realization as well as mark-ups, mainly overhead costs and profit. Overhead costs and profit constitute a considerable part of the bid price and their improper calculation can significantly influence the financial situation of the company. In literature and in practice one can find many definitions and ways of determining overhead costs and profit. The article presents research results concerning defining and calculating overhead costs and profit by Polish contractors, carried out twice – in 2004 and 2010. They were compared with similar studies performed in other countries. The article also presents mathematical methods created by the authors, by means of which overhead costs and profit can be calculated more precisely than by the popular methods commonly employed by Polish contractors.